Intravenous Dexamethasone as an Adjuvant in Reducing Post-Operative Pain, Nausea, Vomiting and Shivering - Sangeeta Bansal Agrawal; Rohit Tiwari; Pranay Gupta (Academia Anesthesiologica International, 2019)
Background: Outcome of any surgery depends on perioperative care of patients. Aim of our study was to hasten the recovery by reducing most common encountered complications like Pain, Nausea, Vomiting and Shivering seen in immediate postoperative period by using single dose of intravenous Dexamethasone. Subjects and Methods: This prospective randomized controlled study enrolled 120 patients scheduled for surgery under general anaesthesia. Patients were randomly divided in two groups. Group 1 was given intravenous Dexamethasone 8mg (2ml) preoperatively and Group 2 was given intravenous normal saline(2ml).Patients were observed for 24 hours post operatively to record postoperative pain, nausea , vomiting, shivering, haemodynamic and other complications .Results: Both the groups were similar in demographic data. Patients from study group had statistically significant lower postoperative VAS for pain at 0hrs, 6hrsand 24hrs (P value 0.048). Similarly patients of study group was also found to have statistically significant low incidence of Nausea (P value 0.022), Vomiting (P value 0.033) and shivering grade (P value 0.008) in first postoperative day. There was lesser requirement of rescue analgesia and rescue antiemetic in patients pre-treated with Dexamethasone (P value <0.05). There were no significant variation in blood sugar levels or any other side effects noted in any patients. Patients from study group were more comfortable postoperatively as compared to control group. Conclusion: Intravenous 8mg Dexamethasone given preoperatively was found to reduce immediate postoperative pain, shivering, nausea and vomiting without any significant side effects.